Quality analysis of cooking oil (RBD Palm Olein) based on PORAM standard specifications - Lestari, Puji; Yusuf, Faisal; Fahdi, Firdaus (Science Midwifery, 2024)
RBD Palm olein is processed from the fruit of the oil palm (Elaeis guineensis) and used as cooking oil. RBD Palm Olein is widely used for cooking oil in many countries. Quality is an important and useful characteristic of edible oil commodities and their transactions from a business aspect. This study aims to analyze the quality of cooking oil based on PORAM (The Palm Oil Refiners Association of Malaysia) specification. Quality parameters requirements as listed in the Palm Oil Refinery Association of Malaysia (PORAM) specification such as moisture and impurities (M&I), free fatty acids (FFA), slip melting point (SMP), iodine value (IV) and colour were determined. There were six samples in total and the quality analysis result is compared with the PORAM Specification. All samples are fulfilled PORAM specifications.